2013
DOI: 10.1001/jamapediatrics.2013.36
|View full text |Cite
|
Sign up to set email alerts
|

Suctioning and Length of Stay in Infants Hospitalized With Bronchiolitis

Abstract: Importance: Hospitalizations of infants for bronchiolitis are common and costly. Despite the high incidence and resource burden of bronchiolitis, the mainstay of treatment remains supportive care, which frequently includes nasal suctioning. Objective: To examine the association between suctioning device type and suctioning lapses greater than 4 hours within the first 24 hours after hospital admission on length of stay (LOS) in infants with bronchiolitis. Design: Retrospective cohort study. Data were extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 17 publications
3
35
0
2
Order By: Relevance
“…The difference of the length of hospital stay between two groups was not statistically significant (p value .06), which correlated with other studies 19,20 .…”
Section: Resultssupporting
confidence: 90%
“…The difference of the length of hospital stay between two groups was not statistically significant (p value .06), which correlated with other studies 19,20 .…”
Section: Resultssupporting
confidence: 90%
“…Although multiple studies have demonstrated that oxygen saturation influences admission rates, 31,32 other factors such as poor oral intake and need for aggressive suctioning may be important drivers of LOS. Studies have described an association between decreased oral intake and nasal suctioning with LOS in infants with bronchiolitis, [33][34][35] and our interventions did not have any impact on suctioning practices or improving oral intake for patients. The median time to medically ready in our study was also ,25 hours on our intervention unit; it is possible that reducing LOS further may be challenging.…”
Section: Discussionmentioning
confidence: 52%
“…Although suctioning the nares may provide temporary relief of nasal congestion or upper airway obstruction, a retrospective study reported that deep suctioning 150 was associated with longer LOS in hospitalized infants 2 to 12 months of age. The same study also noted that lapses of greater than 4 hours in noninvasive, external nasal suctioning were also associated with longer LOS.…”
Section: Figurementioning
confidence: 99%